2010
DOI: 10.1007/s00421-010-1598-0
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic signal and force comparisons during maximal voluntary isometric contraction in water and on dry land

Abstract: This study was designed to compare surface electromyographic (sEMG) signal and force production during maximal voluntary isometric contractions (MVCs) in water and on dry land. The reproducibility of sEMG and isometric force measurements between water and dry land environments was also assessed. Nine women performed MVC for elbow flexion and extension, hip flexion, and extension against identical fixed resistance in both environments. The sEMG signal from biceps brachii, triceps brachii, rectus femoris, and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 25 publications
(51 reference statements)
1
22
1
Order By: Relevance
“…Other researchers also found similar neuromuscular responses between environments during maximal isometric contractions for diVerent muscles (Alberton et al 2008;Carvalho et al 2010;Pinto et al 2010). Besides, our results are in accordance with Kelly et al (2000) who found no diVerences in the EMG activity from the supraspinatus, infraspinatus, subscapularis and deltoid muscles during shoulder Xexion between environments at higher velocity.…”
Section: Neuromuscular Responsessupporting
confidence: 95%
“…Other researchers also found similar neuromuscular responses between environments during maximal isometric contractions for diVerent muscles (Alberton et al 2008;Carvalho et al 2010;Pinto et al 2010). Besides, our results are in accordance with Kelly et al (2000) who found no diVerences in the EMG activity from the supraspinatus, infraspinatus, subscapularis and deltoid muscles during shoulder Xexion between environments at higher velocity.…”
Section: Neuromuscular Responsessupporting
confidence: 95%
“…In contrast with the results obtained in this study, Pinto et al (2010) found no significant changes in the electromyographic activity on land or in water during maximal voluntary isometric contractions of the biceps muscles, triceps brachii, rectus femoris and biceps femoris.…”
Section: Rectus Femoris Biceps Femoriscontrasting
confidence: 99%
“…When the EMG signal is properly carried out in the aquatic environment, the data integrity is maintained compared with data acquisition on the land (Castillo-Lozano and Cuesta-Vargas, 2013). Volume 31, Number 1, p. 19-25, 2015 A study by Pinto et al (2010) showed no differences in the amplitude of the myoelectric signal for maximum strength exercises performed in water and on land. On the other hand, other studies found a reduction of the muscle electrical activity during exercises in the water compared with on the ground (Cuesta Vargas et al, 2013a;Fujisawa et al, 1998;Kelly et al, 2000;Masumoto et al, 2004;Pöyhönen et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown high EMG reliability for aquatic exercises. 18,33,34 To acquire the surface EMG signals produced during exercise, an ME6000P8 (Mega Electronics, Ltd., Kuopio, Finland) biosignal conditioner was used.…”
Section: Experimental Sessionmentioning
confidence: 99%
“…9,[17][18][19] However, the literature on the effect of producing maximum velocity of movement using different devices is scant. Regarding the effect of velocity on muscular activation in a water environment, it is known that when using the same device, greater velocity induces more activation, especially if submaximum velocity is compared with maximum velocity.…”
mentioning
confidence: 98%